Perancangan Sistem Manajemen Absensi Online dengan Barcode scanner Menggunakan Power Apps - Niam Shofi; Iskandar Fitri; Agus Iskandar (KITA Institute, 2021)
Attendance is a form of attachment or obligation between employees and companies, especially at PT. IDX with work locations for project employees who are spread across many companies and different office locations, namely in Jakarta and Bandung. Based on this study, an online-based employee attendance system using the barcode scanner method is applied, because previously employees were still using manual signatures with insufficient security systems and concerns about data leakage, with this attendance system employees do not need to sign manually, resulting in fraud. attendance can be avoided. The application of QR code technology to the employee attendance system can speed up the employee attendance process. Besides that, it can also help make it easier for the HRD Team in managing employee attendance reports to make it more effective and efficient.